2011
DOI: 10.1007/s00128-011-0407-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Analytical Methods and Residue Patterns of Pymetrozine in Aster scaber

Abstract: Residues of the polar pesticide pymetrozine were compared using two methods: hydromatrix and liquid–liquid extraction (LLE). The biological half-life and the final residue level were investigated using Aster scaber over a 10-days cultivation period. The respective biological half-lives of the pesticide were 4.2 and 3.5 days at the recommended and double dose. The final residue levels were 1.28 and 1.98 mg kg−1, respectively, at the same application rate of pymetrozine according to the GAP standard of the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…2 LC-MS/MS chromatograms in MRM acquisition mode of pymetrozine spiked in matrices (0.01 mg kg −1 ): a standard b water; c soil; d rice straw; e brown rice; and f rice husk residue was below limit of detection after 21 days. The results showed that a sharp decline of residue level in the first 2 weeks, which was similar to that 79.02 and 87.28 % of the initial residue levels had already dissipated after 10 days of application at the recommended dose and double dose, respectively (Hong et al 2011). …”
Section: Dissipation Of Pymetrozine In Rice Field Ecosystemsupporting
confidence: 64%
“…2 LC-MS/MS chromatograms in MRM acquisition mode of pymetrozine spiked in matrices (0.01 mg kg −1 ): a standard b water; c soil; d rice straw; e brown rice; and f rice husk residue was below limit of detection after 21 days. The results showed that a sharp decline of residue level in the first 2 weeks, which was similar to that 79.02 and 87.28 % of the initial residue levels had already dissipated after 10 days of application at the recommended dose and double dose, respectively (Hong et al 2011). …”
Section: Dissipation Of Pymetrozine In Rice Field Ecosystemsupporting
confidence: 64%
“…The pesticide dilution effect (f') was calculated from remaining pesticide and weight of peach over 10 days [8]. For the two cases in which growth rate was not considered and those in which the 1.77-fold growth rate was considered, the patterns of residue in relation to growth at the triple dose are given in Figure 6.…”
Section: Teflubenzuronmentioning
confidence: 99%
“…As pymetrozine is widely used across the world, many papers on the analysis of pymetrozine in soils, terrestrial plants and meat products are available. Pymetrozine residues are usually extracted from different matrices using acetonitrile (Camino-Sanchez et al, 2010;Dias et al, 2013;Zhang, Zhang, Xu, Li, & Wang, 2015) and methanol (Hong, Cho-Rong, Jong-Sung, & Kyu-Seung, 2011). The extracts were cleaned up using solid-phase extraction (Zhao et al, 2014) or liquid-liquid partitioning with organic solvent such as dichloromethane (Zhang et al, 2015), ethyl acetate (Hong et al, 2011), or dispersive solid-phase extraction (Cabizza, Satta, Falconi, Onano, & Uccheddu, 2007).…”
mentioning
confidence: 99%
“…Pymetrozine residues are usually extracted from different matrices using acetonitrile (Camino-Sanchez et al, 2010;Dias et al, 2013;Zhang, Zhang, Xu, Li, & Wang, 2015) and methanol (Hong, Cho-Rong, Jong-Sung, & Kyu-Seung, 2011). The extracts were cleaned up using solid-phase extraction (Zhao et al, 2014) or liquid-liquid partitioning with organic solvent such as dichloromethane (Zhang et al, 2015), ethyl acetate (Hong et al, 2011), or dispersive solid-phase extraction (Cabizza, Satta, Falconi, Onano, & Uccheddu, 2007). The commonly used analytical instruments for pymetrozine are HPLC (De, Commissati, Gritti, Catellani, & Suman, 2015;Hong et al, 2011); LC-MS/MS (Camino-Sanchez et al, 2010;Dias et al, 2013;Fernandes et al, 2014) and GC (Jang et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation